FRI0317 NOVEL CLASSIFICATION OF IDIOPATHIC INFLAMMATORYMYOPATHIES BASED ON DISTINCTIVE FEATURES AND AUTOANTIBODIES: ANALYSIS OF 67 KOREAN PATIENTS. (June 2019) - Chung, Sang Wan; Yoo, In Seol; Yoo, Su-Jin; Kim, Jinhyun; Kang, Seong Wook; Shim, Seungcheol; Kwon, Mihye; Joung, Chung-Il; Hong, Seung-Jae; Lee, Yeon-Ah
Abstract : Background: SinceBohan and Peter first described their diagnostic criteria foridiopathic inflammatorymyopathies (IIM) in 1975, new discoveries suchas myositis-specific and myositis-associated autoantibodies (Abs) have been made. Objectives: To investigate correlations between specificmyositis Abs and their frequenciesand clinical associationsacross different IIM groups, collectively demonstrating theutility of the new clinicoserologic classification in Koreanadult patients with IIM. Methods: We conducted a multicenter cohort study including 67adult patients (age≥18 years) who have been diagnosed as IIM by ENMC criteria.Immunoblot assay with Euroline strip(EUROIMMUN, Germany)was performed using the sera of definite deramatomyositis (DM, n=36), definite polymyositis (PM, n=25), amyopathic DM (n=4), DM sine dermatitis (n=1), and immune mediated necrotizing myopathy (IMNM, n=1). Patients were classifiedbased on three classifications: 1) novel clinicoserologic classification suggested by Troyanov et al. in 2017. 2) 2017 EULAR/ACR classification criteria. 3) 2004 European neuromuscular center (ENMC) criteria.Associations ofmyositis Absand clinical subsets of IIM were investigated. Results: The distribution of the various IIM differed strikingly from those using the 3 classifications (Fig1 ). According to the 2004 ENMC classification and 2017 EULAR/ACR classification criteria, DM and PM was the most and the second frequent entities (DM: 55.2%, 56.7%; PM: 35.8%, 37.3%). But, using the new clinicoserologic classification, overlapmyositis(OM) is the major type of IIM and the frequency of PM is significantly decreased.Anti-ARS Abs specificity included anti-Jo-1(16.4%), -OJ(4.6%), -EJ(6.2%) -PL-7(3.1%), and -PL-12(4.6%). Interstitial lung disease was closely associated with anti-MDA5, and anti-ARS Abs, while DM-specific skin lesion was frequently observed in patients with anti-TIF1γ and anti-ARS Abs. Sevenpatients with cancer-associated DM were identified. They were positive for anti-TIFγ (5/7) and anti- SRP(3/7) (table 1 ). Conclusion: Novel classification based on distinctive features and new myositis Absreflects the clinical phenotype of IIM better. Establishment of a system routinely available to screen myositis Abs is needed. Thiswill be beneficial to providemore precise diagnosis and proper management for patients with IIM. Reference: [1] Jean-Luc Senecal, Jean-Pierre Raynauld, Yves Troyanov. A New Classification of Adult Autoimmune Myositis. Arthritis Rheum2017;69:878-884. Disclosure of Interests: None declared